Assessment of the state of the computer system based on the hurst exponent - Semenov, Sergei; Gavrylenko, Svitlana; Chelak, Victor Vladimirovich (Technical University of Sofia, 2017)
The method of identifying abnormal behavior of computer systems based on the Hurst exponent is examined in this report. Results of the research suggest the possibility of using the Hurst exponent for identifying the anomalous behavior of computer systems in the overall system to detect malicious software.
Keywords: Hurst exponent; computer security; computer virus; abnormal behavior